2011
DOI: 10.1209/0295-5075/93/28006
|View full text |Cite
|
Sign up to set email alerts
|

Stall force of polymerizing microtubules and filament bundles

Abstract: Abstract. -We investigate stall force and polymerization kinetics of rigid protofilaments in a microtubule or interacting filaments in bundles under an external load force in the framework of a discrete growth model. We introduce the concecpt of polymerization cycles to describe the stochastic growth kinetics, which allows us to derive an exact expression for the stall force. We find that the stall force is independent of ensemble geometry and load distribution. Furthermore, the stall force is proportional to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
65
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(77 citation statements)
references
References 29 publications
11
65
1
Order By: Relevance
“…Some arguments, based on detailed balance criterion, have also been given in Refs. [26] and [29] to show similar result of f (N ) s ∝ N for their respective models on cytoskeletal filaments. However, we demonstrate that a simple calculation based on elementary statistical mechanics, for essentially kinetic processes, leads to the same conclusion.…”
Section: Collective Stall Force For Multiple Cytoskeletal Filamensupporting
confidence: 52%
See 2 more Smart Citations
“…Some arguments, based on detailed balance criterion, have also been given in Refs. [26] and [29] to show similar result of f (N ) s ∝ N for their respective models on cytoskeletal filaments. However, we demonstrate that a simple calculation based on elementary statistical mechanics, for essentially kinetic processes, leads to the same conclusion.…”
Section: Collective Stall Force For Multiple Cytoskeletal Filamensupporting
confidence: 52%
“…On the theoretical and computational front, there are a number of very detailed models for understanding the force-velocity dynamics of a single biofilament [50][51][52][53], as well as a few that try to model the dynamics of multiple biofilaments [26,[28][29][30][31][54][55][56]. Some of these theoretical studies have demonstrated that the stall force of multiple, non-interacting filaments without ATP/GTP dynamics, scales linearly with the number of filaments [26,[28][29][30]54].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of actin filaments to sustain in supercritical conditions a compressive force has predominantly been justified with the aid of the rigid living filament model, effectively a one dimensional model, both for the single filament case and for bundles of parallel filaments [4,[6][7][8][9][10][11][12][13]. The 1D filaments which are fluctuating in length as a result of (de)polymerizing steps are hitting a fluctuating obstacle usually subject to load by producing instantaneous kicks which result into a time averaged force biasing the obstacle brownian motion.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] To do so, extant theories (and many simulations as well) have appealed to approximations that are not generally justified by the underlying chemical kinetics. For example, it is commonly assumed that nonequilibrium considerations are important only for the discrete, driven part of the ratcheting process; all other degrees of freedom are imagined to follow adiabatically.…”
mentioning
confidence: 99%